2020
DOI: 10.1159/000509342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mental Health Background and Nutrition Intake on Medium-Term Weight Loss in Japanese Patients Undergoing Laparoscopic Sleeve Gastrectomy

Abstract: <b><i>Objectives:</i></b> Bariatric surgery is the most effective weight loss therapy, and recently laparoscopic sleeve gastrectomy (LSG) is gaining popularity worldwide. On the other hand, patients undergoing bariatric surgery have a high prevalence of mental disorders. A Japanese nationwide survey reported high prevalence of mental disorders in patients with low percent total weight loss (%TWL) and also in those with high %TWL. The aim of this study was to investigate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…According to a review conducted by Sarwer and Heinberg (2020), up to 50% of these patients reported preoperative disordered eating, particularly loss of control over eating. Findings about the impact of comorbidities on weight loss differ, with some studies reporting that preoperative mental illness and BE were not associated with lower weight loss (Friedman et al, 2019;Saiki et al, 2020), and others showing that these comorbidities affected postoperative outcomes (Marek et al, 2017;Müller et al, 2019;Sarwer and Heinberg, 2020). In a study with a sample of bariatric surgery patients, Williamson et al (2018) found a significant ADHD by emotion self-regulation interaction on weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…According to a review conducted by Sarwer and Heinberg (2020), up to 50% of these patients reported preoperative disordered eating, particularly loss of control over eating. Findings about the impact of comorbidities on weight loss differ, with some studies reporting that preoperative mental illness and BE were not associated with lower weight loss (Friedman et al, 2019;Saiki et al, 2020), and others showing that these comorbidities affected postoperative outcomes (Marek et al, 2017;Müller et al, 2019;Sarwer and Heinberg, 2020). In a study with a sample of bariatric surgery patients, Williamson et al (2018) found a significant ADHD by emotion self-regulation interaction on weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…If the former is the main issue, re-operation should be considered. When the latter is the case, inadequate protein intake, snacking habits, and consumption of soft drinks are reported to adversely affect weight loss effect of the surgery [ 51 , 194 ]. With regard to alcohol consumption, patients should be encouraged to drink in moderation, because the risk of alcoholism increases after surgery [ 197 ].…”
Section: Preoperative Managementmentioning
confidence: 99%
“…Furthermore, because surgery shrinks the stomach, patients become incapable of eating large amounts of food, which often result in grazing, a common cause of weight regain [ 229 ]. It has also been pointed out that patients with mental disorders tend to polarize into two groups after surgery: those without any drastic weight loss and those with excessive weight loss [ 51 ]. Therefore, it is recommended that the medical team stuff (mainly physicians and surgeons) simulate these postoperative changes such as psychiatric symptoms and eating behavior changes after surgery [ 226 , 230 ].…”
Section: Preoperative Managementmentioning
confidence: 99%
See 2 more Smart Citations